THE USE OF SONG IN INCREASING STUDENTS’ VOCABULARY - Tiouw, Angelina; Kamagi, Sarah; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Language is an essential component of human existence. According to Brown (2001), language is an arrangement of erratic, vocal images that allows everyone in a culture to communicate or work together. In many ways, English are very important to Indonesian education. Because it is taught as a foreign language, students are able to speak and write the language. studying English, which provides students with numerous advantages. The students have access to numerous informational resources in English. This is because almost all technology is written in English. Therefore, it is essential for students to learn English in order to keep up with the most recent technology used in education. The purpose of this study was to determine how Song could improve students’ vocabulary. This quantitative study consists of a single group pre- and post-test. Using a mean score formula, the author analyzed the students’ performance on the pre- and post-tests. The author discovered that the students’ mean score before treatment was 50.5, and their mean score after treatment was 79.5. It is evident that the students’ post-test score was higher than their pre-test score. According to the data gathered, students in VIII C of SMP Negeri 4 Tondano’s vocabulary can be improved through song.